أهمية أدب الزوائد في دراسات الحديث: تحليل مقارن لكتاب "مجمع الزوائد" للهيثمي و"إتحاف الخيرة المهرة" للبوصيري والمطالب العالية لإبن حجر: The Significance of Zawa'id Literature in Hadith Studies: A Comparative Analysis of Al-Haythami's "Majma' al-Zawa'id" and Al-Busiri's "Ithaf al-Khirah al-Mahrurah" - Dr. Zainab Sadiq; Dr Hidayat Khan (Al Manhal Research Journal, 2024)
This article explores the concept of Zawa'id literature within the field of Hadith studies, emphasizing its critical role in the preservation and transmission of Prophetic traditions. Zawa'id, or supplementary reports, are additional narrations found in specific collections that are not present in more widely recognized sources. The discussion centers on two pivotal works: "Majma' al-Zawa'id" by Al-Haythami and "Ithaf al-Khirah al-Mahrurah" by Al-Busiri. The article begins with an introduction to Zawa'id, outlining its importance for scholars researching the Sunnah. It highlights how these texts contribute to a more comprehensive understanding of Hadith literature. Al-Haythami's "Majma' al-Zawa'id," published in the 19th century, encompasses 42 books and organizes numerous hadiths systematically. The author’s background, significant teachers, and notable works are summarized, providing context for his contributions to Islamic scholarship. Conversely, Al-Busiri’s "Ithaf al-Khirah al-Mahrurah" is presented, detailing its methodology and scholarly significance. The article compares the two works, examining their approaches to Zawa'id extraction, the criteria for inclusion, and the presentation of chains of narrators. Key features such as the volume of narrations and their classifications are discussed, alongside scholarly reception and the impact these texts have had on subsequent hadith research. Ultimately, the analysis concludes that Zawa'id literature serves as a vital resource for Hadith scholars, enriching the corpus of Islamic tradition and ensuring the integrity of the Sunnah. The comparative study of Al-Haythami and Al-Busiri's methodologies underscores the evolution of hadith scholarship and the importance of diverse sources in the preservation of religious knowledge.